SCIENTIFIC AND THEORETICAL FOUNDATIONS OF APPLYING STEAM EDUCATION TECHNOLOGY IN PRIMARY GRADES (Scientific journal of the Fergana State University, 2025)
This article analyzes the scientific and theoretical foundations of developing spatial imagination (spatial thinking) in primary school students by applying STEAM education technologies, as well as the most effective methods of implementing these technologies in practice. It explores the origins and development stages of the STEAM approach, international experiences, and the current state of its adoption in Uzbekistan’s education system. The paper also provides various definitions of “imagination” and describes methods to enhance students’ spatial perception through the use of multimedia and integrated approaches in the educational process.